Three classes of ligands each bind to distinct sites on the orphan G protein-coupled receptor GPR84. Issue 1 (December 2017) - Mahmud, Zobaer; Jenkins, Laura; Ulven, Trond; Labéguère, Frédéric; Gosmini, Romain; De Vos, Steve; Hudson, Brian; Tikhonova, Irina; Milligan, Graeme
Abstract Medium chain fatty acids can activate the pro-inflammatory receptor GPR84 but so also can molecules related to 3, 3′-diindolylmethane. 3, 3′-Diindolylmethane and decanoic acid acted as strong positive allosteric modulators of the function of each other and analysis showed the affinity of 3, 3′-diindolylmethane to be at least 100 fold higher. Methyl decanoate was not an agonist at GPR84. This implies a key role in binding for the carboxylic acid of the fatty acid. Via homology modelling we predicted and confirmed an integral role of arginine172, located in the 2nd extracellular loop, in the action of decanoic acid but not of 3, 3′-diindolylmethane. Exemplars from a patented series of GPR84 antagonists were able to block agonist actions of both decanoic acid and 3, 3′-diindolylmethane at GPR84. However, although a radiolabelled form of a related antagonist, [3 H]G9543, was able to bind with high affinity to GPR84, this was not competed for by increasing concentrations of either decanoic acid or 3, 3′- diindolylmethane and was not affected adversely by mutation of arginine172 . These studies identify three separable ligand binding sites within GPR84 and suggest that if medium chain fatty acids are true endogenous regulators then co-binding with a positive allosteric modulator would greatly enhance their function in physiological settings.